2018
DOI: 10.1371/journal.pone.0204459
|View full text |Cite
|
Sign up to set email alerts
|

Independent association of HLA-DPB1*02:01 with rheumatoid arthritis in Japanese populations

Abstract: ObjectiveRheumatoid arthritis (RA) is a chronic autoimmune disease characterized with joint destructions; environmental and genetic factors were thought to be involved in the etiology of RA. The production of anti-citrullinated peptide antibodies (ACPA) is specifically associated with RA. DRB1 is associated with the susceptibility of RA, especially ACPA-positive RA [ACPA(+)RA]. However, a few studies reported on the independent associations of DPB1 alleles with RA susceptibility. Thus, we investigated the inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Moreover, Furukawa et al . identified an association between DPB102:01 and ACPA (+) RA in Japanese populations [ 17 ]. In addition, O'Brien et al reported that the A allele at rs9277535 was associated with decreased HLA-DPB1 mRNA levels in the normal human liver [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Furukawa et al . identified an association between DPB102:01 and ACPA (+) RA in Japanese populations [ 17 ]. In addition, O'Brien et al reported that the A allele at rs9277535 was associated with decreased HLA-DPB1 mRNA levels in the normal human liver [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the precise determination of an individual's HLA class I and II gene polymorphisms with the use of the NGS approach is considered more efficient compared to the previously used HLA typing methods (Hosomichi et al, 2015;Sanchez-Mazas and Meyer, 2014). As a consequence, this information could be used for better donor-recipient matching, thus reducing the percentage of transplantation failure (Hosomichi et al, 2015) and in disease association studies (Akassou & Bakri, 2018;Augusto & Hollenbach, 2022;Aureli et al, 2015;Fakhkhari et al, 2023;Furukawa et al, 2018;Gough & Simmonds, 2007;McCanlies et al, 2003;Mounzer et al, 2019;Takeno, 2022). This, in turn, may benefit the increase of the available transplant number, worldwide, which can further assist in shortening the recipients' waiting lists (Mangum & Caywood, 2022;Sheldon & Poulton, 2006).…”
Section: Introductionmentioning
confidence: 99%